Self-Efficacy and Stress Management of Nurses in a Rural Health Unit - Angelito E. Alvarado; King Ferdinand A. Valdez; Jared Noah M. Valdez; Dennielle Pauline G. Valdez; Mikaela C. Viernes; Gladys T. Villarta; Jessa Grace L. Yamo; Ysabel V. Ygnacio (Humanistic Network for Science and Technology (HNST), 2022)
Research Rural Health Unit nurses are the generalists who are professional in nursing communities, they are always been stressful and should give double effort and more patience to the client they are dealing with. Self-efficacy and stress management among nurses of Rural Health Units focused on the significant relationship of the self-efficacy and stress management of nurses amidst of pandemic. This study used a quantitative method specifically descriptive correlational. In the analysis of the variables, frequency and percentage, weighted mean, pearson r moment of correlation and chi square test were used. The questionnaire was researchers-made consisted of three dimensions of stress management; the cognitive dimension, affective dimension, and motivational dimension and the self-efficacy of a nurse using the likert scale. Data were collected by a valid and reliable questionnaire using an online platform. The findings reveals that RHU nurses had no significant relationship between stress management and self-efficacy among the respondents. It also reveals that no significant relationship between stress management and self-efficacy when grouped according to the respondent’s profile. It concluded that age, educational attainment, civil status and years in service did not influence the stress management and self-efficacy of the nurses. To the RHU nurses it will be a great help to identify ways of handling their stress and improving their self-efficacy in delivering quality nursing care and to serves as their basis to be aware in times of stress occurrence. Keywords: self-efficacy; stress; management